Register Analysis of English Biology Texts: A Corpus-Based Exploratory Study of Grammar - Borza, Natália (Working Papers in Language Pedagogy, 2013)
While considerable research has been conducted on describing the discourse features of academic writing in the field of biology, there is hardly any research available on the register specific features of textbooks written for secondary students, in particular on those of biology textbooks. The present quantitative investigation aims to fill this niche by means of developing an analytical instrument capable of providing data that describe the dominant grammatical features of English language biology texts used in the instruction of Hungarian students in a bilingual secondary school in Budapest. The results of the study reveal that biology texts for secondary students are less complex in terms of grammar than general English reading texts for intermediate (B2) learners. The findings are hoped to be of assistance to biology ESP teachers and general English teachers instructing in a bilingual secondary school alike.